Pengaruh Kualitas Pelayanan Dan Kinerja Karyawan Terhadap Kepuasan Pasien (Studi Kasus Pada Pasien Rawat Inap RS.Pelabuhan Jakarta) - Riski Amelia; Rodhiyah Rodhiyah (Universitas Diponegoro, 2016)
Hospital is a health facility conducting personal health services includes promotive, preventive, curative, and rehabilitative services providing inpatient, outpatient, and emergency services. Many factors that affect patient satisfaction, one of them is the quality of service and employee performance. This study aims to determine the effect of service quality and employee performance to patient satisfaction. The primary data used by providing questionnaires to hospitalized patient with a total of 100 respondents are determined using a Slovin formula table. Respondents are taken using accidental sampling and purposive sampling method.Results and Discussion. Quality of service to both patient satisfactions with average score of 3,754, employee performance with average score of 3,772 and satisfactory patient satisfaction with average score of 3,794. Service quality significantly influence towards patient satisfaction (p <0,05) with a correlation coefficient of 0,507, R2 0,257 and t count value of 5.829 > t table 1,6606. Employee performance significantly influence towards patient satisfaction (p<0,05) with a correlation coefficient of 0,462, R2 0,214 and t count value of 5,163 > t table 1,6606. But the results of recapitulation of service quality regarding duration of the service before it is sent to the infirmary has a result below the average i.e. 3,67. Service quality and employee performance significantly influence towards patient satisfaction with correlation coefficients of 0,578, R2 0,334 and F count test results of 24,361 > F table 3,090.In conclusion and suggestions, service quality and employee performance significantly influence towards patient satisfaction either partially or simultaneously. It is suggested to hospitals to improve service quality and employee performance, maximize service in dealing with patients, improving the readiness and responsiveness, accelerate delivery time to patient care space, and the arrival of the doctor in charge. It is useful to give satisfaction to the patients who are undergoing medical treatment at the hospital.